Business Management Analysis at Krisna Textile Based on Interview Results - Rhandi Rhiswandi; Yus Djunaedi Rusli (Journal Tourism Nomic, 2026)
This study aims to explore the business practices and operational management of Krisna Textile, a retail textile business located in Purwakarta, Indonesia. The research was conducted using a qualitative descriptive approach through direct interviews and field observations with the business owner. Krisna Textile was established in 2013 with initial capital contributed by three founders and currently operates independently under the ownership of Mr. Zhae Sanuman Danwangi. The business focuses on purchasing various types of fabric from suppliers and reselling them to consumers through retail and wholesale channels. The findings indicate that the company initially relied on word-of-mouth marketing but recently began adopting social media promotion through TikTok to reach a broader market. Krisna Textile has expanded its market distribution to several regions in Indonesia, including Riau, Medan, and Balikpapan. However, the business has experienced a decline in performance during the 2024–2025 period, which has led management to plan operational adjustments, including reducing the size of the sales area. The study highlights the importance of strategic promotion, operational efficiency, and balanced business development to maintain sustainability in the retail textile industry.